A novel development route for cyano-based high performance thermosetting resins via the strategy of functional group design-dicyanoimidazole resins. (26th August 2020) - Hu, Jianghuai; Yang, Wenjie; Tan, Wei; Liang, Bo; Xiao, Hang; Li, Renke; Lv, Jiangbo; Zeng, Ke; Yang, Gang
Abstract: A novel class of high-performance resins based on dicyanoimidazole (DCI) reaction group with flexible structural modifiability was developed for the first time. As a pioneering work, propyl-containing DCI model monomer, namely 1, 1′-(propane-1, 3-diyl) bis (1H-imidazole-4, 5-dicarbonitrile) (PDBDCI), was successfully synthesized and studied. Results showed that PDBDCI have higher curing reactivity compare with phthalonitrile and benzonitrile, and the cured PDBDCI have excellent thermal and thermal mechanical properties compare with the most of thermoset resins including aliphatic-containing phthalonitrile resins. These results confirm that DCI group can serves as an ideal cross-linking group for high-performance thermosetting resins. Graphical abstract: Image 1 Highlights: A novel class of high-performance resins based on dicyanoimidazole (DCI) reaction group was developed for the first time. DCI model monomer have higher curing reactivity compare with phthalonitrile and benzonitrile monomers. The cured DCI resins have excellent thermal and thermal mechanical properties compare with the most of thermoset resins.